Seed Priming With Protein Hydrolysates Improves Arabidopsis Growth and Stress Tolerance to Abiotic Stresses - Sorrentino, Mirella; De Diego, Nuria; Ugena, Lydia; Spíchal, Lukáš; Lucini, Luigi; Miras-Moreno, Begoña; Zhang, Leilei; Rouphael, Youssef; Colla, Giuseppe; Panzarová, Klára (Frontiers in Plant Science, 2021)
The use of plant biostimulants contributes to more sustainable and environmentally friendly agricultural practices, and offers an alternative to synthetic protectants used to alleviate the adverse effects of stress. Protein hydrolysates-based biostimulants have been reported to improve plant growth and reduce the adverse effect of abiotic stress in different crops. However, very little is known about their mode of action, how plants perceive their application and which metabolic pathways are activating. Here we used multi-trait high-throughput screening approach based on simple RGB imaging and combined with untargeted metabolomics to screen and understand the mode of action of protein hydrolysates-based biostimulants in Arabidopsis plants grown in optimal and in salt-stress conditions (0, 75 or 150 mM NaCl). Eleven protein hydrolysates from different protein sources were used as priming agents in Arabidopsis seeds in three different concentrations (0.001, 0.01 or 0.1 µl ml-1). Growth and development-related traits as early seedling establishment capacity, growth capacity under stress and photosynthetic performance of the plants were dynamically scored throughout and at the end of the growth period. To effectively classify the functional properties of the 11 products a Plant Biostimulant Characterization (PBC) index was used, which helped to characterize a biostimulant mode of action based on its contribution to the plant development and stress tolerance and to categorize the products as plant growth promoters, growth inhibitors and/or stress alleviator. Out of 11 products, two were identified as highly effective growth regulators and stress alleviators because they showed a PBC index always above 0.51. Using the untargeted metabolomics approach, we showed that plants primed with these best performing biostimulants had reduced contents of stress related molecules (such as flavonoids and terpenoids, and some degradation/conjugation compounds of plant growth regulators such as cytokinins, auxins, gibberellins, etc.), which alleviated the salt stress response-related growth inhibition.